Multiple Factors Influencing Healthy Performance for Pre-professional and Professional Classical Violinists: An Exploratory Study Focusing on Physical Health - Steemers, Suze; Veen, Mario; van Middelkoop, Marienke; Bierma-Zeinstra, Sita M. A.; Stubbe, Janine H. (Frontiers in Psychology, 2022)
Musculoskeletal complaints are common in pre-professional and professional classical violinists and these complaints can affect violinists’ performance. Therefore, it is important to identify the factors that contribute to healthy performance in this population. Qualitative studies with a variety of stakeholders are able to provide insights from different perspectives into factors influencing healthy performance for the pre-professional and professional classical violinist. In the current small-scale, exploratory study, semi-structured interviews were conducted with various stakeholders; two classical violin students, one classical violin teacher, a physiotherapist, a professional classical violinist, who is also a performance coach, and a health specialist who also graduated as a professional classical violist. Thematic analysis was conducted using Atlas.ti 9. We identified six themes that were indicated as important by the participants in terms of ensuring healthy performance for the pre-professional and professional classical violinist. The themes were: 1) physical aspects (involved in playing the violin); 2) practice routine and techniques; 3) interaction between physical and mental aspects; 4) culture; 5) role of the main subject teacher; and 6) preventive measures. Furthermore, when asked specifically about the development of a physical screening tool, the participants indicated that such a tool should include multiple factors covering various regions of the body, the inclusion of a questionnaire on risk-factors, and follow-up measurements. Also, collaborations between health professionals and main subject teachers were recommended as part of the screening tool to increase commitment of participating students. The results of the current study are based on the opinions, attitudes, and ideas of a small, selected group of participants only and cannot be generalized to a wider group of violinists. More research is needed regarding factors influencing healthy performance, before conservatoires and professional orchestras can develop programs for a healthy playing environment for pre-professional and professional violinists.